2022
DOI: 10.1039/d2cs00110a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical approaches for electronic doping in photovoltaic materials beyond crystalline silicon

Abstract: This review highlights the recent advances of chemical approaches for electronic doping to aid the future development of next-generation photovoltaic materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 434 publications
0
8
0
Order By: Relevance
“…[34] The dopant and semiconductor could also form a charge-transfer complex through orbital hybridization to achieve charge transfer. [36] And it is expected to be utilized in PSCs by improving electrical properties of metal halide perovskites and promoting charge transport. For example, tetrachloro-1,2-benzoquinone (TCBQ) was inserted into the organic sublattice of 2D perovskite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] The dopant and semiconductor could also form a charge-transfer complex through orbital hybridization to achieve charge transfer. [36] And it is expected to be utilized in PSCs by improving electrical properties of metal halide perovskites and promoting charge transport. For example, tetrachloro-1,2-benzoquinone (TCBQ) was inserted into the organic sublattice of 2D perovskite.…”
Section: Introductionmentioning
confidence: 99%
“…Electron acceptor molecule is an important dopant that can receive electrons from the valence band of semiconductor and leave holes in semiconductor, thus optimizing the electrical properties of semiconductor [34] . The dopant and semiconductor could also form a charge‐transfer complex through orbital hybridization to achieve charge transfer [36] . And it is expected to be utilized in PSCs by improving electrical properties of metal halide perovskites and promoting charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…14,30 The incorporation of charge effects induced by electronic doping is considered as an effective strategy of tailoring the fundamental optical, magnetic, electronic, and catalytic properties of materials. [31][32][33][34] For semiconductors devoid of free charge carriers, the dopant-induced charge effects can modify the band structure and redox potential of the Fermi level (E f ) to meet the requirements for efficient SERS substrates. It has been demonstrated that the group 1 elements (H, Li, Na, and K) with small ionic radii can be easily intercalated into the interlayer or channels of a host lattice, thus generating signicant charge effects while maintaining structural integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical doping of semiconductor layers is a key strategy for improving the performance of electronic devices because doping-related shifts of the Fermi level ( E F ) can increase charge carrier densities in the layers by orders of magnitude. Doped films of conjugated polymers including poly­(3-hexylthiophene) (P3HT) find their applications in organic and perovskite photovoltaic devices and photodetectors as well as in thermoelectrics . Furthermore, P3HT is a well-studied model system to better understand the fundamental processes at work in doping-related charge transfer and the generation of mobile holes in the semiconductor host.…”
Section: Introductionmentioning
confidence: 99%